Integration of Islamic Values in Preserving Cakalele Culture as Character Education - Nurul Fathinah F. Hamid; Amanan Soleman; Musa Marengke (International Islamic Studies Development and Research Center (IISDRC), 2026)
This study aims to discover the forms of Cakalele cultural preservation, analyze the mechanisms of integrating Islamic educational values, and identify opportunities and challenges within the process. A qualitative case study approach was employed. Data were collected through participatory observation, in-depth interviews with teachers, students, and cultural figures, as well as documentation analysis. Data were analyzed interactively through reduction, display, and conclusion drawing, with source and method triangulation to ensure validity. Findings reveal that Cakalele preservation is implemented through extracurricular activities and school performances. The integration of Islamic values is achieved by reinterpretation of cultural symbols, such as the parang symbolizing intellectual sharpness and faith, and teamwork representing ta’awun (mutual cooperation). Opportunities include institutional commitment, community support, and students’ enthusiasm for local culture. Challenges involve perceptions linking Cakalele to pre-Islamic traditions, limited facilities, and scheduling conflicts with academic activities. This study highlights that local cultural preservation can serve as an effective medium for character education in Islamic schools, provided it is accompanied by contextual and dialogical reinterpretation. The findings contribute to curriculum development based on local wisdom and strategies for cultural communication in Islamic education.